Risk factors for previously unknown meticillin-resistant Staphylococcus aureus carriage on admission to 13 surgical wards in Europe. - Pan, A; Lee, A; Cooper, B; Chalfine, A; Daikos, G; Garilli, S; Goossens, H; Malhotra-Kumar, S; Martínez, J; Patroni, A; Harbarth, S (2013)
BACKGROUND: Early identification of meticillin-resistant Staphylococcus aureus (MRSA) carriers may be helpful for clinical and epidemiological reasons. AIM: To identify and compare risk factors of previously unknown MRSA carriage on admission to 13 surgical wards in France, Greece, Italy, and Spain. METHODS: The study was a prospective observational cohort study which enrolled consecutive patients screened for MRSA on admission to surgical wards. Sociodemographic data, comorbidities and possible risk factors for MRSA were recorded. A multivariate logistic regression model was used to predict probabilities of previously unknown MRSA colonization on admission based on patient characteristics. Prediction rules for MRSA carriage were developed and evaluated using the c-statistic. FINDINGS: Of 2901 patients enrolled, admission screening identified 111 (3.8%) new MRSA carriers. Independent risk factors for MRSA carriage were urinary catheterization (odds ratio: 4.4; 95% confidence interval: 2.0-9.9), nursing home residency (3.8; 1.9-7.7), chronic skin disease (2.9; 1.5-5.8), wounds/ulcers (2.4; 1.5-4.0), recent hospitalization (2.2; 1.5-3.3), diabetes (1.6, 1.02-2.5), and age >70 years (1.5; 1.03-2.3). However, risk factors varied between centres. The c-statistic for the common prediction rule for all centres was 0.64, indicating limited predictive power. CONCLUSIONS: Risk profiles for MRSA carriers vary between surgical wards in European countries. Identifying local risk factors is important, as a common European prediction rule was found to be of limited clinical value.